ANALISA KEBUTUHAN ENERGI MINIMUM UNIVERSITAS LANCANG KUNING - HALILINTAR, MASNUR PUTA; S.T, MONICE (Human Sustainability Procedia, 2018)
The need for electrical energy to support the vision of the University of Lancang Kuning Unggulin 2030 is a necessity. Excellence according to the assessment standards of the Directorate of Higher Education in 2015 following the results of the ranking of universities in Indonesia is determined by four categories. First; quality of human resources; Second; quality management; Third; quality of student activities; and Fourth; quality research and scientific publications.Activities of these four criteria come from campus activities undertaken by lecturers, students and campus management associated with electrical energy. It is undeniable that it is impossible that research activities of lecturers, campus management and student activities are not related to electrical energy. Evidently at this time, Unilak experienced energy deficit and become a problemthat resulted in not optimum teaching and learning process, management activities related to IT devices.Referring to Permenristek No15 of 2015 on Lecturer and Student Ratio rules and Unilak’s vision of 2030 superior need to be studied the minimum energy consumption requirement at University of Lancang Kuning to maintain optimal achievement of the rating criteria.In the initial phase begins by collecting data and inventory Asset energy use in each Faculty, and other facilities then make estimates of powerusage according to exixting dataThe results show that the energy used today is still below the standard energy that is convenient for the activities tridharma college. The minimum installed energy available for an average room is 1,160 wat for a room with a size of 64 m2. With conditions like this should be re-calculated to get the ideal minimum energy to support the activities of tri dharma college to Unilak Unggul 2030